2022
DOI: 10.1002/ctm2.1061
|View full text |Cite
|
Sign up to set email alerts
|

PARK7 deficiency inhibits fatty acid β‐oxidation via PTEN to delay liver regeneration after hepatectomy

Abstract: Background & aims Transient regeneration–associated steatosis (TRAS) is a process of temporary hepatic lipid accumulation and is essential for liver regeneration by providing energy generated from fatty acid β‐oxidation, but the regulatory mechanism underlying TRAS remains unknown. Parkinsonism‐associated deglycase (Park7)/Dj1 is an important regulator involved in various liver diseases. In nonalcoholic fatty liver diseased mice, induced by a high‐fat diet, Park7 deficiency improves hepatic steatosis, but its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…After screening by MS analysis for fatty acid metabolism‐related proteins that interact with ALR, 7 candidate proteins were detected, including HADHB , CPT1A , TECR , HSD17B4 , ACSL4 , HSD17B12 , and HACD3 (Table 2, Figure 7H). Among these proteins, CPT1A, the known rate‐ limiting enzyme of FAO, 35 was reported to reduces M1 macrophage infiltration in CPT1A‐knockin mice 36 . In the idiopathic pulmonary fibrosis model, M1 macrophages disrupted fatty acid metabolism, which manifested as reduced FAO activity and decreased CPT1A expression 37 .…”
Section: Resultsmentioning
confidence: 99%
“…After screening by MS analysis for fatty acid metabolism‐related proteins that interact with ALR, 7 candidate proteins were detected, including HADHB , CPT1A , TECR , HSD17B4 , ACSL4 , HSD17B12 , and HACD3 (Table 2, Figure 7H). Among these proteins, CPT1A, the known rate‐ limiting enzyme of FAO, 35 was reported to reduces M1 macrophage infiltration in CPT1A‐knockin mice 36 . In the idiopathic pulmonary fibrosis model, M1 macrophages disrupted fatty acid metabolism, which manifested as reduced FAO activity and decreased CPT1A expression 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Peroxisomes, fatty acid metabolism, and liver regeneration are interconnected. 70 The decrease in peroxisomes showed that aged livers have a reduced ability to withstand oxidative stress and that lipid metabolism and fatty acid oxidation are thus compromised. Such compromised fatty acid metabolism leads to a decreased energy supply, but liver regeneration is energy-consuming, which decreases the capability for liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism has an important role in liver regeneration [42,45]. Indeed, fatty acid oxidation is the main source of energy for liver regeneration, and inhibition of fatty acid β-oxidation has been reported to delay liver regeneration after hepatectomy [46]. Cholesterol affects liver regeneration by regulating cell cycle progression [47], and steroids inhibit liver regeneration by suppressing TNF-α and IL-6 overproduction and hepatocyte DNA synthesis [48,49].…”
Section: Discussionmentioning
confidence: 99%